Prodanova rastna funkcija - Cedilnik, Anton (Zbornik gozdarstva in lesarstva, 1983)
In the article there are collected formulas of growth function ?$y=x^2/(a+bx+ cx^2)$? where the coefficients ?$a,b,c$? are optional. Addet are some instructions on the application of this function to numerical data.
Keywords: approximation; aproksimacija; forestry; gozdarstvo; growth function; matematika; mathematics; Michail Prodan; rastna funkcija